Climate-smart agricultural research center to partner with UN’s rural investment agency to increase food security in rural areas - International Center for Tropical Agriculture (2017)
Rome, 13 February 2017 – A statement of intent between the International Center for Tropical Agriculture (CIAT) and the International Fund for Agricultural Development (IFAD) promises to boost resilience to climate change and improve the livelihoods of thousands of smallholder farmers around the world. The partnership will serve to maximize the work of both agencies by making new climate-smart technologies and innovations developed by CIAT research available to the smallholder farmers participating in IFAD-supported projects in developing countries.